Ser médico negro : (re) significando identidades sociais e étnicas - Beato, Rosaura Bandeira (2006)
This is an exploratory study on the exercise of the medical profession by black individuals and the strategies some of them have had to resort in order to confront social and / or racial inequalities. It is an analysis of the careers of eight black physicians of different generations who were both trained in medical colleges, and, since their graduation, continued to live and work in the state of Espírito Santo. Its purpose is to identify in the careers of these black doctors situations consequent on their ethnic origin, that is, to identify situations in their daily work in which they suffered racial discrimination; to identify the strategies they have themselves created in defiance of the racial discrimination and the social inequalities they have come across in their daily work; and to investigate the relationship between their experiences of racial discrimination and social inequality intheir daily work and their consciousness of their psychical suffering as brought about by these experiences. The empirical data were collected through non-directive interviews and the analysis of contents applied to the answers of the interviewed. The subject of this study --- which is “what does it mean being a black doctor ?” --- was approached through the sociological concepts of racial prejudice, racism and racial discrimination. The study also includes the analysis of the motivation of these doctors’ option for the medical profession, their training, and their professional practice, all this in connection with their psychical suffering and the ways they were led to construct in order to confront racial prejudice, racism and racial discrimination. It also deals with possible differences among these black doctors in the ways they built up the subjectivity of being black persons in the medical profession, and built up their social and ethnic identities. It has been possible in this study to examine the hypothesis that assumed the existence of racial prejudice, racism, and racial discrimination in our society. Its conclusion, in short, is that the medical profession is not among those ones to which black people have any easy access. But the possibility of achieving personal recognition for hard work and excellence in perfomance have led some black individuals to choose this profession as a means of improving their economic and symbolic capital. However, being a black doctor has not offered them any protection against racial prejudice, racism and racial discrimination.